Adoption of Virtual Reality technologies among fans of football: Exploring a new form of interaction in the Match Day - Langaro, D.; Oliveira, P.; Loureiro, S. M. C. (Global Marketing Conference at Seoul, 2020)
Virtual Reality (VR) applications are growing into an increasing market size, with VR technologies being used in manufacturing, medicine, art, navigation, education and gaming (Loureiro, Guerreiro, Eloy, Langaro & Panchapakesan, 2019). In sports industry, the adoption of VR is still in a very early stage, despite being acknowledged as a promising technology for various applications, among them, improving fans´ experience while watching sports games (Kim & Ko, 2019). The perspective that VR may simulate the real experience of attending the stadium in a matchday raises a common interest among managers and researchers, given the potential size of the opportunity. Due to its embryonic stage, no study so far has explored this topic from the perspective of understanding the triggers that influence its adoption. The current study addresses this research opportunity and explores the antecedents for the adoption of VR in improving fans´ experience while watching sports games. Moreover, the current study focuses on football. Else than being responsible for an expressive business size, with the European football leagues accounting for more than €28 billion, the largest share of revenues in football derives from negotiating the rights for broadcasting the games to fans´ homes (Delloite, 2019). This reveals the strategic relevance of exploring opportunities related to those fans who currently watch football games at home and enjoy experiences that are quite limited in flow and sense of presence (Kim & Ko, 2019). An immersive VR football experience simulating the match day was developed (in concept board), including avatars and covering the pre-match, the match itself, including life statistics and exclusive view points and the post-match phases. In total, 203 respondents have evaluated the concept regarding their interest and the antecedents for its adoption, as proposed by the Extended Technology Acceptance Model (Manis & Choi, 2019; Davis, Bagozzi, & Warshaw, 1989). Results were analysed using structural equation modelling (Smart PLS), which allowed predicting purchase and use intentions. Findings suggest that perceived usefulness, perceived enjoyment and attitudes towards the technology are strong predictors of the outcomes. Moreover, the results support the potential of virtual reality and its integration in sports. This study paves the way to further research on this matter and provides several insights and recommendations for sports organisations. Among the limitations are the medium used for testing and the experience designed, which by definition has guided respondents evaluations.